2018
DOI: 10.1007/s13744-017-0582-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Foraging Experience Affect the Responses of the Predator Dicyphus hesperus Knight to Prey-Induced Volatiles?

Abstract: The predatory mirid bug Dicyphus hesperus Knight (Hemiptera: Miridae) is a native North America species with high potential as biological control agent of the potato psyllid, Bactericera cockerelli Sulcer (Hemiptera: Triozidae), which is a major solanaceous pest. Olfactory responses of D. hesperus to volatiles from plants infested with the potato psyllid and the effect of foraging experience on search efficacy were studied. Using a Y-tube olfactometer, we found that naïve females had no preference in choice te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Bernays et al (2004) find that generalist (phytophagous) species spend more time dispersing and assessing resources and have shorter feeding bouts compared to specialists. The food specialization resulting from information management could be genetic (Dumont et al, 2017a) and/or be the result of previous experience (Lins et al, 2014;Rim et al, 2017;Lima-Espindola et al, 2018). An alternative strategy to complex information management for omnivorous predators would be to be less selective and more opportunistic.…”
Section: Optimizing Zoophytophagous Predators Through Diet Specializamentioning
confidence: 99%
See 1 more Smart Citation
“…Bernays et al (2004) find that generalist (phytophagous) species spend more time dispersing and assessing resources and have shorter feeding bouts compared to specialists. The food specialization resulting from information management could be genetic (Dumont et al, 2017a) and/or be the result of previous experience (Lins et al, 2014;Rim et al, 2017;Lima-Espindola et al, 2018). An alternative strategy to complex information management for omnivorous predators would be to be less selective and more opportunistic.…”
Section: Optimizing Zoophytophagous Predators Through Diet Specializamentioning
confidence: 99%
“…Lins et al (2014) observed that both M. pygmaeus and N. tenuis responded positively to plants infested by their prey [whitefly Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) and the tomato borer Tuta absoluta Meyrick (Lepidoptera: Gelechiidae)]. Moreover, experienced predators are more reactive to plant volatiles than naïve individuals (Lins et al, 2014;Rim et al, 2017;Lima-Espindola et al, 2018). Hence, prey-specialized or highly-zoophagous individuals could be more reactive to HIPVs than their plant-specialized or lowly-zoophagous counterpart due to 1) increased experience with hosts infested with prey and/or 2) genetic correlation between zoophagy and olfactory response to HIPVs (Nachappa et al, 2010).…”
Section: Interactions With Host Plantsmentioning
confidence: 99%
“…Ponsonby and Copland (1995) reported that experienced Chilocorus nigritus (F.) (Coleoptera: Coccinellidae) adults were attracted by prey and the prey's host plants [38]. Naïve predatory mirid bug Dicyphus hesperus Knight (Hemiptera: Miridae) had no preference between uninfested and Bactericera cockerelli Sulcer (Hemiptera: Triozidae) egg-infested tomato; however, D. hesperus females with foraging experience preferred infested tomato [39]. In addition, the morphological characteristics of plants, such as trichome, leaf color, leaf shape and so on, also affect the seeking behavior of pests and natural enemies [40,41].…”
Section: Discussionmentioning
confidence: 99%